Redo buccal mucosa graft urethroplasty: success rate, oral morbidity and functional outcomes. (11th June 2016) - Rosenbaum, Clemens M.; Schmid, Marianne; Ludwig, Tim A.; Kluth, Luis A.; Dahlem, Roland; Fisch, Margit; Ahyai, Sascha
Abstract : Objectives: To determine the success rate, oral morbidity and functional outcomes of redo buccal mucosa graft urethroplasty (BMGU) for treatment of stricture recurrence after previous BMGU. Patients and Methods: We included 50 patients who underwent redo BMGU between February 2009 and September 2014. Patients' charts and non‐validated questionnaires were reviewed. The primary endpoint was success rate, defined as stricture‐free survival. Stricture recurrence was defined as any postoperative claims of catheterization, dilatation, urethrotomy or repeat urethroplasty, or a maximum urinary flow rate <15 mL/s, and a stricture was consecutively verified in a combined cysto‐urethrogram or cystoscopy at annual follow‐up visit. The secondary endpoint was oral morbidity. Additional endpoints were erectile function, urinary continence and patients' satisfaction. Results: Redo BMGU was performed for bulbar (71.4%) or penile (28.6%) recurrent strictures. The mean (median; range) follow‐up was 25.6 (15.5; 3–70) months. Stricture recurrence occurred in 18.0% of patients within a mean (median; range) of 13.8 (9.0; 3–36) months. Stricture‐free survival at 12, 24 and 36 months was 91.2, 86.2 and 80.8%, respectively. The majority of the patients (97.0%) reported no or only mildly changed salivation or problems in opening of the mouth. Severe or very severe oral numbness occurred in 13.5% of patients. Oral problems in daily life were a moderate or severe burden to 13.6 and 2.7% of the patients, respectively, while 75.0% of the patients reported improved quality of life compared with preoperative status. Conclusions: Thes uccess rate and oral morbidity of redo BMGU are almost the same as outcomes of primary BMGU. Oral numbness was the most frequently reported oral disorder.